Colours and microplastics: Bridging the gap between art, science and sustainability - Asim N.; Zulkifli A.A.B.; Nazri N.S.; Torkashvand M.; Badiei M.; Rajabi A.; Mohammad M. (Elsevier B.V., 2025)
The significant influence of colour on life and the numerous advantages of plastics over metals, ceramics, wood and other materials result in the incorporation of colour into polymers through a variety of techniques, including internally and externally. The widespread use of plastics, inappropriate trash disposal and inefficient recycling result in a substantial release of plastic into the environment. Environmental factors, such as heat, light, moisture, chemicals and wind, can degrade polymers, altering the composition, structure and morphology to a certain degree. This situation can result in the production of microplastics (MPs) and nanoplastics (NPs) and associated chemicals. Ecosystems are seriously endangered by materials resulting from continuous deterioration, fragmentation and ageing of plastics. Majority of the commonly used plastics are coloured, underscoring the importance of closely monitoring coloured MPs. The influence of colour on MP formation, environmental effect, identification and waste management topics has not received enough attention. This review article addresses various concerns regarding coloured MPs, including their abundance, leaking, ageing, waste management and sustainability. Moreover, this work is based on research from field-based articles on plastics, MPs and coloured MPs. In the context of plastic pollution, future strategies for more effective mitigation of coloured MPs were also explored. Furthermore, this work attempts to assist in creating a clear road map for decision-making, selecting the optimal option for a given goal and developing a plan for expanding and improving an existing strategy. ? 2024